Productivity of grafted papaya growing under open environment in the Mexican pacific - Álvarez-Hernández Juan Carlos; Castellanos-Ramos Javier Zaragoza; Aguirre-Mancilla Cesar Leobardo (Folia Horticulturae)
The phytosanitary problems and the complex floral biology influence the fruit quality and productivity of papaya. Use of grafting mitigates adverse aspects, becoming a complementary activity of crop. The objective of this study was to evaluate the agronomic behaviour of grafted papaya plants. Two experiments were carried out. In the first experiment, the treatments were derived from six rootstock/scion combinations and four controls, based on commercial genotypes. In the second experiment, four rootstocks and two genotypes formed eight rootstock/scion treatments, and two controls were used. The morphological variables as well as the qualitative and productive variables of fruits were recorded. Results showed that plant height was maintained or reduced in some treatments, whereas stem girth and leaf numbers in grafted treatments were increased. The fruit quality was not influenced by grafting. In the productivity, the grafted plants showed higher fruit production. For an example, the Rootstock 'MSXJ' × Scion 'Maradona' and the Rootstock 'BS2' × Scion 'Maradol'>40 kg · plant−1 and almost 9 kg · m–2, respectively; and the Rootstock 'Robusta' × Scion 'Maradol' treatment was higher than the other treatments, reaching 38.39 kg · plant–1 and 8.53 kg · m–2, in Experiments 1 and 2, respectively. Grafting on papaya positively changed the morphological variables, increased the number of fruits per plant in grafted plant treatments, as well as yield per area, surpassing controls by 25% and 22% in both experiments, respectively.